2009
DOI: 10.3168/jds.2008-1848
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of tuberculosis in Irish Holstein-Friesian dairy herds

Abstract: Information is lacking on genetic parameters for tuberculosis (TB) susceptibility in dairy cattle. Mycobacterium bovis is the principal agent of tuberculosis in cattle. The objective of this study was to quantify the genetic variation present among Irish Holstein-Friesian dairy herds in their susceptibility to M. bovis infection. A total of 15,182 cow and 8,104 heifer single intradermal comparative tuberculin test (SICTT, a test for M. bovis exposure and presumed infection) records from November 1, 2002, to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 20 publications
9
72
2
1
Order By: Relevance
“…However, a similar finding was found in cattle that were classified as reactors after being subjected to the gamma interferon test (DEFRA, 2005). Other explanations include genetic/breed differences in susceptibility to bTB (Bermingham et al, 2009;Driscoll et al, 2011) and the higher within-herd transmission coefficient in dairy herds compared to non-dairy herds (Alvarez et al, 2012) There was no significant association between the number of lifetime moves or the number of animals purchased in the last three years and the VL status and bTB status of reactor animals in this study. The importance of movement and purchase of cattle as a risk factor to bTB infection has been supported by several studies (Gilbert et al, 2005;Ramirez-Villaescusa et al, 2009;Ramirez-Villaescusa et al, 2010).…”
Section: Discussioncontrasting
confidence: 46%
“…However, a similar finding was found in cattle that were classified as reactors after being subjected to the gamma interferon test (DEFRA, 2005). Other explanations include genetic/breed differences in susceptibility to bTB (Bermingham et al, 2009;Driscoll et al, 2011) and the higher within-herd transmission coefficient in dairy herds compared to non-dairy herds (Alvarez et al, 2012) There was no significant association between the number of lifetime moves or the number of animals purchased in the last three years and the VL status and bTB status of reactor animals in this study. The importance of movement and purchase of cattle as a risk factor to bTB infection has been supported by several studies (Gilbert et al, 2005;Ramirez-Villaescusa et al, 2009;Ramirez-Villaescusa et al, 2010).…”
Section: Discussioncontrasting
confidence: 46%
“…Indeed, it is only recently that effort has been directed towards quantifying the host genetic influence (Bermingham et al 2009;Brotherstone et al 2010).…”
Section: Host Genetic Variationmentioning
confidence: 99%
“…Previous studies have demonstrated genetic variation in resistance to bTB (Bermingham et al . 2009; Brotherstone et al . 2010) and have shown the feasibility of genomic selection for bTB resistance using information from markers dispersed throughout the genome (Tsairidou et al .…”
Section: Introductionmentioning
confidence: 99%